Less influence of body mass index on bone mineral density of radius as compared to proximal femur: Possible role in the diagnosis of osteoporosis - Asli, Isa; Sheikhnezami, Mahsa; Qutbi, Mohsen; Farsad, Faraneh; Asli, Sadaf; Ranji, Shahla; Karami, Maryam (World Journal of Nuclear Medicine, 2020)
It has been shown that body mass index (BMI) and obesity may affect the mineral density of bones, regionally on weight-bearing bones or systemically through hormones and cytokines. The objective of this study was to evaluate the effect of BMI on bone mineral density (BMD) of the radius. In this cross-sectional study, 260 patients, 233 postmenopausal women and 27 men over 50, were included who underwent a bone densitometry scanning using dual-energy X-ray absorptiometry after obtaining an informed consent. The scanning was performed in three areas (i.e., spine, proximal femur, and radius), then densitometric data (BMD, T- and Z-score) were extracted. Regression analysis was performed to evaluate the effect of independent variables of age, gender, and BMI on the BMD of the above regions. By grouping the patients in two categories (BMI <25 as normal or underweight and BMI >25 as overweight and obese), the discordance in the diagnosis following the inclusion of radius into interpretation (diagnosis based on 2 vs. 3 areas), was assessed by an agreement test. The study is approved by the ethics committee of the university. Of 260 participants in the present study, mean and standard deviation for age were 61.48 ± 8.95 for all patients, 65.81 ± 10.59 for male and 60.98 ± 8.62 for women. An increasing effect of BMI was found to be statistically significant in weight-bearing areas (total femur and femoral neck) and BMI increase was not associated with increased BMD of radius. An agreement test between two diagnoses is used that showed a discordance of 28.5% in diagnosis (diagnosis based on 2 vs. 3 areas) with a kappa coefficient of 0.547 (P = 0.001). In total, 25.4% was minor discordance and 3.1% was major discordance. Based on the results of this study, it is concluded that the BMI is not associated with increased BMD in bones that are not weight bearing, such as radius. Therefore, it may be preferred to include the densitometric data of radius into the diagnosis.
Keywords: Body mass index; bone mineral density; obesity; osteoporosis; radius